2017
DOI: 10.4103/jpn.jpn_80_17
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric head injury: A study of 403 cases in a tertiary care hospital in a developing country

Abstract: Introduction:Traumatic brain injury (TBI) in children is a significant cause of morbidity and mortality worldwide. Falls are the most common type of injury, followed by motor vehicle-related accidents and child abuse.Aims and Objectives:The aim and objective of this study was to elucidate the various modes of injury, prognostic factors, complications, incidence of various modes of injury, and outcome in TBI in pediatric population.Materials and Methods:Patients with TBI, 18 years or less in age, managed in our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…Considering the overall outcome in our cohort of pediatric TBI patients, a GOSE score of 7 or 8 could be observed in 64% of cases. However, an unfavorable outcome (GOSE 1-4) was still present in 10% of pediatric TBI patients which is comparable to numbers from single-center studies reported from India (10%) and the United States (16%) (13,14). Independent predictors for an unfavorable outcome six months after TBI in pediatric patients who were admitted to the regular ward or ICU were GCS and the occurrence of secondary insults in multivariate analysis.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Considering the overall outcome in our cohort of pediatric TBI patients, a GOSE score of 7 or 8 could be observed in 64% of cases. However, an unfavorable outcome (GOSE 1-4) was still present in 10% of pediatric TBI patients which is comparable to numbers from single-center studies reported from India (10%) and the United States (16%) (13,14). Independent predictors for an unfavorable outcome six months after TBI in pediatric patients who were admitted to the regular ward or ICU were GCS and the occurrence of secondary insults in multivariate analysis.…”
Section: Discussionsupporting
confidence: 71%
“…Similar to the results from the core dataset, brain injury was classified as serious to severe in most cases (AIS 3 (2-4) ). GCS ratings were also similar to the CENTER-TBI core study with a GCS of 15 (14)(15) in the admission stratum and 12 (7)(8)(9)(10)(11)(12)(13)(14)(15) in the ICU stratum. On brain CT, an abnormality was detected in 49% of pediatric TBI patients in the registry dataset.…”
Section: Comparison With the Center-tbi Registry Datasetsupporting
confidence: 62%
See 1 more Smart Citation